Solvent Extraction of Lead (II) and Its Separation from Bismuth (III) - Aher, H.R.; Gunjal, P.S.; Kuchekar, S.R.; Chavan, M.B. (Asian Journal of Chemistry, 2010)
Solvent extraction behaviour of Iead(II) with n-octylaniline in differentorganic solvents from halogen acid solutions was investigated. A schemefor separation of lead and bismuth is developed. The nature of probableextracted species has been established. The method has been applied forseparating and estimating lead from synthetic mixtures. The proposedmethod is simple, rapid and also selective.